Interleukin (IL)-22 receptor 1 is over-expressed in primary Sjogren's syndrome and Sjögren-associated non-Hodgkin lymphomas and is regulated by IL-18. (3rd June 2015) - Ciccia, F; Guggino, G; Rizzo, A; Bombardieri, M; Raimondo, S; Carubbi, F; Cannizzaro, A; Sireci, G; Dieli, F; Campisi, G; Giacomelli, R; Cipriani, Paola; et al.
Summary: The aim of this study was to elucidate more clearly the role of interleukin (IL)-18 in modulating the IL-22 pathway in primary Sjögren's syndrome (pSS) patients and in pSS-associated lymphomas. Minor salivary glands (MSGs) from patients with pSS and non-specific chronic sialoadenitis (nSCS), parotid glands biopsies from non-Hodgkin lymphomas (NHL) developed in pSS patients, were evaluated for IL-18, IL-22, IL-22 receptor 1 (IL-22R1), IL-22 binding protein (IL-22BP) and signal transducer and activator of transcription-3 (STAT-3) expression. MSGs IL-22R1-expressing cells were characterized by confocal microscopy and flow cytometry in pSS, nSCS and healthy controls. The effect of recombinant IL-18 and IL-22 on peripheral blood mononuclear cells (PBMCs) from pSS and nSCS was studied by flow cytometry and reverse transcription–polymerase chain reaction (RT-PCR). MSGs of pSS and NHL were characterized by an imbalance between IL-22 and IL-22BP protein expression, with IL-18 and IL-22BP being expressed in a mutually exclusive manner and IL-18 and IL-22R1 being correlated directly. Aberrant expression of IL-22R1, induced by IL-18, was observed only among tissue and circulating myeloid cells of pSS patients and macrophages of NHL tissues of pSS patients, but not nSCS. IL-22R1 expression on PBMC of pSS was functional, as its stimulation with recombinant IL-22 significantly up-regulated the expression of STAT-3, IL-17 and IL-22. An IL-18-dependent aberrant expression of IL-22R1 on cells of haematopoietic origin seems to be a specific immunological signature of patients with pSS and pSS-associated lymphomas.